Fiscal Strategies to Tackle the Shadow Economy: A Literature Review - Adrinata, Reza (Jurnal Pajak dan Keuangan Negara (PKN), 2025)
The shadow economy is a significant challenge in fiscal policy management, especially in developing countries such as Indonesia. This unrecorded economic activity leads to lost tax revenue potential and disrupts the effectiveness of economic policy. This study aims to evaluate fiscal strategies that can be used to reach and tax activities in the shadow economy sector with a circulation-based approach. The method used is a literature study of more than 20 international journals and institutional reports, with SWOT analysis techniques to assess the strengths, weaknesses, opportunities, and threats of the reviewed policies. The results show that the monetary approach, particularly the Currency Demand Approach and the MIMIC Model, is effective as an indirect indicator to estimate the size of the shadow economy. Fiscal strategies such as presumptive taxation, digital payment system integration (such as QRIS), and data estimation-based tax intensification are considered complementary and have the potential to broaden the tax base. International case studies from Germany, India, and Turkey emphasise the importance of synergies between fiscal reform, digital transformation, and strong governance. The findings provide a basis for developing more adaptive, inclusive, and data-driven fiscal policies in Indonesia.